2. Jahresbericht des Instituts für Organisationsökonomik - Alexander Dilger; Stephanie Kiefer (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2012)
Dies ist der 2. Jahresbericht des vor zwei Jahren gegründeten Instituts für Organisationsökonomik. Berichtszeitraum sind das Wintersemester 2011/2012 und das Sommersemester 2012. Nach einer Vorstellung des Instituts, seiner Professoren und Mitarbeiter wird über die Forschung, Lehre und Weiteres des Instituts berichtet. – – This is the second annual report of the Institute for Organisational Economics, founded two years ago. It informs about the winter semester 2011/2012 and the summer semester 2012. After a presentation of the institute, its professors and employees, it reports on research, teaching and further activities of the institute.
Keywords: 650